Purification in an active form of the phage phi 29 protein p4 that controls the viral late transcription. - Barthelemy, I (1987)
The phage phi 29 protein p4, that controls viral late transcription, was highly purified from Escherichia coli cells harbouring a gene 4-containing plasmid. This protein, representing about 6% of the total cellular protein, was obtained in a highly purified form. The protein was characterized as p4 by amino acid analysis and NH2-terminal sequence determination. The purified protein was active in an in vitro transcription assay, allowing specific initiation of transcription at the phi 29 A3 late promoter in the presence of Bacillus subtilis sigma 43-RNA polymerase holoenzyme.